The Exact Timing of Microinjection of Parthenogenetic Silkworm Embryos Is Crucial for Their Successful Transgenesis - Zabelina, Valeriya; Vrchotova, Marketa; Yonemura, Naoyuki; Sezutsu, Hideki; Tamura, Toshiki; Klymenko, Vyacheslav; Sehnal, Frantisek; Zurovec, Michal; Sehadova, Hana; Sauman, Ivo (Frontiers in Physiology, 2022)
The use of parthenogenetic silkworm (Bombyx mori) strains, which eliminate the problem of recombination, is a useful tool for maintaining transgenic clonal lines. The generation of genetically identical individuals is becoming an important tool in genetic engineering, allowing replication of an existing advantageous trait combination without the mixing that occurs during sexual reproduction. Thus, an animal with a particular genetic modification, such as the ability to produce transgenic proteins, can reproduce more rapidly than by natural mating. One obstacle to the widespread use of parthenogenesis in silkworm genetic engineering is the relatively low efficiency of downstream transgenesis techniques. In this work, we seek to optimize the use of transgenesis in conjunction with the production of parthenogenetic individuals. We found that a very important parameter for the introduction of foreign genes into a parthenogenetic strain is the precise timing of embryo microinjection. Our modification of the original method increased the efficiency of transgene injection as well as the survival rate of injected embryos. We also provide a detailed description of the methodological procedure including a graphical overview of the entire protocol.